Boron high thermal conductivity aluminum alloy for automobile box and its production process

By adding modified filler and boron nitride to the aluminum alloy for automobile boxes, the high thermal conductivity of boron aluminum alloy is solved, and the effect of high thermal conductivity and good mechanical properties is achieved, which meets the automobile boxes. lightweight and high performance requirements.

CN118497563BActive Publication Date: 2025-02-11东莞市东兴铝业有限公司
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410493342.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-23
Publication Date
2025-02-11
Estimated Expiration
2044-04-23

AI Technical Summary

Technical Problem

At present, the aluminum alloy material used in automobile boxes is highly brittle and cannot meet the lightweight and high-performance needs of automobiles.

Method used

Using a production process of boron-high thermal conductivity aluminum alloy for automobile boxes, by weighing a specific percentage of raw materials, including aluminum, copper, silicon and magnesium, and melting and stirring under high temperature conditions, adding modified fillers and nitriding Boron forms an aluminum alloy with high thermal conductivity and good mechanical properties.

Benefits of technology

It improves the thermal conductivity and mechanical properties of aluminum alloy, solves the problem of high brittleness of aluminum alloy materials, and meets the lightweight and high-performance needs of automobile boxes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a boron high thermal conductivity aluminum alloy for automobile box and a production process thereof. The following percentage raw materials are taken: 92-93% of aluminum, 1-1.5% of copper, 5-5.5% of silicon and 0.5-1% of magnesium, the raw materials are melted, modified fillers and boron nitride are added, melt blending is performed, a slag remover is added, and static treatment is performed to obtain the boron high thermal conductivity aluminum alloy for automobile box. The modified filler is carbonized during the preparation process so that the three-dimensional structure and the silsesquioxane structure on the surface are carbonized to form a carbon layer doped with sulfur and nitrogen elements and a silicon carbide structure coated between graphene and carbon nanotubes, and then wrapped by copper plating to ensure that the modified filler can be evenly dispersed in the aluminum alloy, and a core-shell structure is formed by using metal and carbon materials, so as to further improve the mechanical properties of the aluminum alloy material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aluminum alloy preparation, and in particular to a boron high thermal conductivity aluminum alloy for automobile boxes and a production process thereof. Background Art

[0002] With the exploration of the world and the need for a better life, cars have become a necessity for today's families. According to statistics, of all the parts in the car, parts made of aluminum alloy materials account for about 17% of the whole vehicle parts. In order to meet the requirements of lightweight and high performance of the car, aluminum alloy materials are used for everything from the car body to the engine cylinder head housing and wheel hub. When a car with an aluminum alloy body collides, the car cannot withstand the impact of the collision, so it cannot effectively protect the safety of the driver and passengers. When the swing arm in the vehicle suspension system passes through a pothole section, it will break and fail due to insufficient swing arm strength; when the piston of the aluminum alloy engine reciprocates, it will cause fatigue fracture failure and cylinder failure of the cylinder body. The above damage occurs mainly because the aluminum alloy parts are subject to malicious interference from the outside world, and the mechanical properties of the aluminum alloy material itself cannot meet the actual working requirements of the parts. Summary of the invention

[0003] The purpose of the present invention is to provide a boron high thermal conductivity aluminum alloy for automobile boxes and a production process thereof, which solves the problem of high brittleness of aluminum alloy materials used in automobile boxes at this stage.

[0004] The purpose of the present invention can be achieved by the following technical solutions:

[0005] A production process of boronized high thermal conductivity aluminum alloy for automobile boxes, specifically comprising the following steps:

[0006] The following raw materials are weighed: 92-93% aluminum, 1-1.5% copper, 5-5.5% silicon and 0.5-1% magnesium, and the aluminum, copper and silicon are added into a graphite crucible, melted at a temperature of 830-850° C., cooled to 650-680° C., magnesium is added, the temperature is raised to 720-750° C., nitrogen is introduced, the temperature is kept for 20-30 minutes, the temperature is lowered to 550-580° C., modified fillers and boron nitride are added, stirred for 5-10 minutes at a rotation speed of 60 r / min, the temperature is raised to 730-760° C., the temperature is kept for 20-30 minutes, and the material is cooled to room temperature to obtain a boron high thermal conductivity aluminum alloy for automobile boxes.

[0007] Furthermore, the amount of the modified filler is 1.25-1.35% of the total mass of aluminum, copper, silicon and magnesium, and the amount of boron nitride is 15-20% of the total mass of aluminum, copper, silicon and magnesium.

[0008] Further, the modified filler is prepared by the following steps:

[0009] Step A1: dispersing carbon nanotubes in mixed acid, reacting for 3-5 hours at a speed of 200-300 r / min and a temperature of 100-105° C., adjusting the pH value to be neutral, filtering and removing the filtrate, dispersing the substrate in DMF, adding DCC and KH550, reacting for 1-3 hours at a speed of 150-200 r / min and a temperature of 30-40° C., to obtain modified carbon nanotubes, dispersing graphene oxide in DMF, adding DCC and KH550, reacting for 3-5 hours at a speed of 150-200 r / min and a temperature of 30-40° C., to obtain modified graphene;

[0010] Step A2: KH570, 4-mercaptobenzimidazole and DMF are mixed evenly, and the mixture is reacted for 1-1.5 hours at a speed of 120-150 r / min and 365 nm under external irradiation to obtain an intermediate 1; modified carbon nanotubes, modified graphene, intermediate 1, tetramethylammonium hydroxide aqueous solution, isopropanol and xylene are mixed, and the mixture is stirred for 10-15 minutes at a speed of 150-200 r / min and a temperature of 20-25° C., and the pH value is adjusted to be neutral, and the stirring is continued for 5-7 days. The filtrate is removed by filtration, and the substrate is dispersed in a hexahydrate magnesium nitrate aqueous solution, and sodium hydroxide is added. The mixture is reacted for 70-75° C. at a speed of 500-800 r / min and a temperature of 100-105° C. to obtain a pretreated filler;

[0011] Step A3: Put the pretreated filler into a muffle furnace, introduce nitrogen, and perform carbonization treatment for 3-5 hours at a temperature of 700-750° C., disperse it in a sodium hydroxide solution, stir it at a speed of 120-150 r / min and a temperature of 90-95° C. for 30-40 minutes, filter out the filtrate, put it into a nitric acid solution, soak it for 10-15 minutes, filter out the filtrate, put it into a copper plating solution, adjust the pH value to 12.5-13, react it at a temperature of 60-65° C. for 30-40 minutes, filter out the filtrate, put it into a disodium ethylenediaminetetraacetic acid solution for passivation treatment for 15-20 minutes, filter out the filtrate and dry it to obtain a modified filler.

[0012] Furthermore, the amount ratio of the carbon nanotubes and the mixed acid described in step A1 is 1g:10mL, the mixed acid is prepared by mixing 98% sulfuric acid with 68% nitric acid in a volume ratio of 3:1, the amount of KH550 is 3-3.5% of the mass of the carbon nanotubes, and the molar ratio of DCC and KH550 is 1.1:1.

[0013] Furthermore, the molar ratio of KH570 and 4-mercaptobenzimidazole described in step A2 is 1:1, the amount ratio of modified carbon nanotubes, modified graphene, intermediate 1, tetramethylammonium hydroxide aqueous solution, isopropanol and xylene is 3g:5g:50mmo l:25mL:30mL:20mL, the amount ratio of substrate, magnesium nitrate hexahydrate aqueous solution and sodium hydroxide is 1g:10mL:0.08mmo l, and the mass fraction of magnesium nitrate hexahydrate aqueous solution is 0.75%.

[0014] Further, the mass fraction of the sodium hydroxide solution described in step A3 is 10%, the mass fraction of the nitric acid solution is 5%, the copper plating solution is 20g of copper sulfate pentahydrate, 40g of disodium ethylenediaminetetraacetate, 9g of formaldehyde and 0.1g of vanadium pentoxide added to water to make a 1L solution, and the mass fraction of the disodium ethylenediaminetetraacetate solution is 5%.

[0015] Beneficial effects of the present invention: The boron high thermal conductivity aluminum alloy for automobile box disclosed in the present application is prepared by weighing the following percentage raw materials: 92-93% aluminum, 1-1.5% copper, 5-5.5% silicon and 0.5-1% magnesium, adding aluminum, copper and silicon into a graphite crucible, melting at a temperature of 830-850°C, cooling to 650-680°C, adding magnesium, heating to 720-750°C, introducing nitrogen, keeping the temperature for 20-30 minutes, cooling to 550-580°C, adding modified filler and boron nitride, stirring at a speed of 60r / min for 5- 10min, heating to 730-760℃, adding slag remover, standing for 20-30min, boron nitride has good thermal conductivity, and the aluminum alloy is a metal product, so that the prepared product has good thermal conductivity, the modified filler is treated with carbon nanotubes as raw materials with mixed acid to make the surface carboxyl, and then KH550 is added under the action of DCC, the amino group on KH550 and the surface carboxyl group dehydrate, so that the surface of the carbon nanotube is grafted with siloxane groups to obtain modified carbon nanotubes, graphene oxide and KH550 are treated under the action of DCC, KH The amino groups on KH550 and the surface carboxyl groups are dehydrated to make the surface of the graphene oxide grafted with siloxane groups to obtain modified graphene. KH570 and 4-mercaptobenzimidazole are reacted under ultraviolet light to make the double bonds on KH570 react with the thiol groups on 4-mercaptobenzimidazole to obtain intermediate 1. The modified carbon nanotubes, modified graphene and intermediate 1 are hydrolyzed to make the siloxane groups hydrolyzed and polymerized to form a silsesquioxane structure between the modified carbon nanotubes, modified graphene and intermediate 1. When dispersed in an aqueous solution of magnesium nitrate hexahydrate, the imidazole groups on intermediate 1 can The pretreated filler is carbonized at high temperature and then placed in a copper plating solution to perform copper plating on the surface, so that the surface is coated with metallic copper. The modified filler is carbonized during the preparation process so that the three-dimensional structure of the surface and the silsesquioxane structure are carbonized to form a carbon layer doped with sulfur and nitrogen elements and a silicon carbide structure coated between the graphene and the carbon nanotubes. The modified filler is then wrapped in copper plating to ensure that the modified filler can be evenly dispersed in the aluminum alloy. At the same time, a core-shell structure is formed with metal and carbon materials, which further improves the mechanical properties of the aluminum alloy material. DETAILED DESCRIPTION

[0016] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0017] Example 1

[0018] A production process of boronized high thermal conductivity aluminum alloy for automobile boxes, specifically comprising the following steps:

[0019] The following raw materials were weighed: 92% aluminum, 1% copper, 5% silicon and 0.5% magnesium. The aluminum, copper and silicon were added into a graphite crucible, melted at 830° C., cooled to 650° C., magnesium was added, the temperature was raised to 720° C., nitrogen was introduced, and the temperature was kept for 20 min. The temperature was lowered to 550° C., modified fillers and boron nitride were added, stirred for 5 min at a speed of 60 r / min, the temperature was raised to 730° C., and the temperature was kept for 20 min. The material was cooled to room temperature to obtain a boron high thermal conductivity aluminum alloy for automobile boxes.

[0020] The amount of the modified filler is 1.25% of the total mass of aluminum, copper, silicon and magnesium, and the amount of boron nitride is 15% of the total mass of aluminum, copper, silicon and magnesium.

[0021] The modified filler is prepared by the following steps:

[0022] Step A1: dispersing carbon nanotubes in mixed acid, reacting at a speed of 200 r / min and a temperature of 100° C. for 3 hours, adjusting the pH value to be neutral, filtering and removing the filtrate, dispersing the substrate in DMF, adding DCC and KH550, reacting at a speed of 150 r / min and a temperature of 30-40° C. for 1 hour to obtain modified carbon nanotubes, dispersing graphene oxide in DMF, adding DCC and KH550, reacting at a speed of 150 r / min and a temperature of 30° C. for 3 hours to obtain modified graphene;

[0023] Step A2: KH570, 4-mercaptobenzimidazole and DMF are mixed evenly, and reacted for 1 hour at a speed of 120 r / min and 365 nm under external irradiation to obtain intermediate 1; modified carbon nanotubes, modified graphene, intermediate 1, tetramethylammonium hydroxide aqueous solution, isopropanol and xylene are mixed, stirred for 10 minutes at a speed of 150 r / min and a temperature of 20° C., the pH value is adjusted to neutral, and stirring is continued for 5 days. The filtrate is filtered to remove the filtrate, the substrate is dispersed in a hexahydrate magnesium nitrate aqueous solution, sodium hydroxide is added, and the reaction is carried out at a speed of 500 r / min and a temperature of 100° C. for 70° C. to obtain a pretreated filler;

[0024] Step A3: The pretreated filler is placed in a muffle furnace, nitrogen is introduced, and carbonization treatment is performed for 3 hours at a temperature of 700°C. The filler is dispersed in a sodium hydroxide solution, stirred for 30 minutes at a speed of 120 r / min and a temperature of 90°C, and the filtrate is filtered to remove the filtrate. The filler is placed in a nitric acid solution and soaked for 10 minutes. The filtrate is filtered to remove the filtrate, and the filler is placed in a copper plating solution. The pH value is adjusted to 12.5. The filler is reacted at a temperature of 60°C for 30 minutes. The filtrate is filtered to remove the filtrate, and the filler is placed in a disodium ethylenediaminetetraacetic acid solution for passivation treatment for 15 minutes. The filtrate is filtered to remove the filtrate and dried to obtain a modified filler.

[0025] The amount ratio of the carbon nanotubes and the mixed acid described in step A1 is 1g:10mL, the mixed acid is prepared by mixing 98% sulfuric acid with 68% nitric acid in a volume ratio of 3:1, the amount of KH550 is 3% of the mass of the carbon nanotubes, and the molar ratio of DCC and KH550 is 1.1:1.

[0026] The molar ratio of KH570 and 4-mercaptobenzimidazole described in step A2 is 1:1, the amount ratio of modified carbon nanotubes, modified graphene, intermediate 1, tetramethylammonium hydroxide aqueous solution, isopropanol and xylene is 3g:5g:50mmo l:25mL:30mL:20mL, the amount ratio of substrate, magnesium nitrate hexahydrate aqueous solution and sodium hydroxide is 1g:10mL:0.08mmo l, and the mass fraction of magnesium nitrate hexahydrate aqueous solution is 0.75%.

[0027] The mass fraction of the sodium hydroxide solution described in step A3 is 10%, the mass fraction of the nitric acid solution is 5%, and the copper plating solution is 20g of copper sulfate pentahydrate, 40g of disodium ethylenediaminetetraacetate, 9g of formaldehyde and 0.1g of vanadium pentoxide added with water to make a 1L solution, and the mass fraction of the disodium ethylenediaminetetraacetate solution is 5%.

[0028] Example 2

[0029] A production process of boronized high thermal conductivity aluminum alloy for automobile boxes, specifically comprising the following steps:

[0030] The following raw materials were weighed: 92.5% aluminum, 1.3% copper, 5.3% silicon and 0.8% magnesium. The aluminum, copper and silicon were added into a graphite crucible, melted at 840°C, cooled to 665°C, magnesium was added, the temperature was raised to 735°C, nitrogen was introduced, the temperature was kept for 25 minutes, the temperature was lowered to 565°C, modified fillers and boron nitride were added, stirred for 8 minutes at a speed of 60 r / min, the temperature was raised to 745°C, the temperature was kept for 25 minutes, the material was cooled to room temperature, and a boron high thermal conductivity aluminum alloy for automobile boxes was obtained.

[0031] The amount of the modified filler is 1.3% of the total mass of aluminum, copper, silicon and magnesium, and the amount of boron nitride is 18% of the total mass of aluminum, copper, silicon and magnesium.

[0032] The modified filler is prepared by the following steps:

[0033] Step A1: dispersing carbon nanotubes in mixed acid, reacting for 4 hours at a speed of 200 r / min and a temperature of 103° C., adjusting the pH value to be neutral, filtering and removing the filtrate, dispersing the substrate in DMF, adding DCC and KH550, reacting for 1.5 hours at a speed of 150 r / min and a temperature of 35° C., to obtain modified carbon nanotubes, dispersing graphene oxide in DMF, adding DCC and KH550, reacting for 4 hours at a speed of 150 r / min and a temperature of 35° C., to obtain modified graphene;

[0034] Step A2: KH570, 4-mercaptobenzimidazole and DMF are mixed evenly, and the reaction is carried out for 1.3 hours at a speed of 120 r / min and 365 nm under external irradiation to obtain intermediate 1; modified carbon nanotubes, modified graphene, intermediate 1, tetramethylammonium hydroxide aqueous solution, isopropanol and xylene are mixed, and stirred for 13 minutes at a speed of 150 r / min and a temperature of 23° C., and the pH value is adjusted to neutral, and stirring is continued for 6 days, and the filtrate is filtered to remove the filtrate, and the substrate is dispersed in a hexahydrate magnesium nitrate aqueous solution, sodium hydroxide is added, and the reaction is carried out at a speed of 500 r / min and a temperature of 103° C. to obtain a pretreated filler;

[0035] Step A3: The pretreated filler is placed in a muffle furnace, nitrogen is introduced, and carbonization treatment is performed for 4 hours at a temperature of 730° C., and then the filler is dispersed in a sodium hydroxide solution, stirred at a speed of 120 r / min and a temperature of 93° C. for 35 minutes, and the filtrate is filtered to remove the filtrate, and then placed in a nitric acid solution, soaked for 15 minutes, the filtrate is filtered to remove the filtrate, and placed in a copper plating solution, the pH value is adjusted to 12.5, and the reaction is carried out at a temperature of 63° C. for 35 minutes, the filtrate is filtered to remove the filtrate, and the filler is placed in a disodium ethylenediaminetetraacetic acid solution for passivation treatment for 18 minutes, and the filtrate is filtered to remove and dried to obtain a modified filler.

[0036] The amount ratio of the carbon nanotubes and the mixed acid described in step A1 is 1g:10mL, the mixed acid is prepared by mixing 98% sulfuric acid with 68% nitric acid in a volume ratio of 3:1, the amount of KH550 is 3.5% of the mass of the carbon nanotubes, and the molar ratio of DCC and KH550 is 1.1:1.

[0037] The molar ratio of KH570 and 4-mercaptobenzimidazole described in step A2 is 1:1, the amount ratio of modified carbon nanotubes, modified graphene, intermediate 1, tetramethylammonium hydroxide aqueous solution, isopropanol and xylene is 3g:5g:50mmo l:25mL:30mL:20mL, the amount ratio of substrate, magnesium nitrate hexahydrate aqueous solution and sodium hydroxide is 1g:10mL:0.08mmo l, and the mass fraction of magnesium nitrate hexahydrate aqueous solution is 0.75%.

[0038] The mass fraction of the sodium hydroxide solution described in step A3 is 10%, the mass fraction of the nitric acid solution is 5%, and the copper plating solution is 20g of copper sulfate pentahydrate, 40g of disodium ethylenediaminetetraacetate, 9g of formaldehyde and 0.1g of vanadium pentoxide added with water to make a 1L solution, and the mass fraction of the disodium ethylenediaminetetraacetate solution is 5%.

[0039] Example 3

[0040] A production process of boronized high thermal conductivity aluminum alloy for automobile boxes, specifically comprising the following steps:

[0041] The following raw materials were weighed: 93% aluminum, 1.5% copper, 5.5% silicon and 1% magnesium. The aluminum, copper and silicon were added into a graphite crucible, melted at 850° C., cooled to 680° C., magnesium was added, the temperature was raised to 750° C., nitrogen was introduced, and the temperature was kept for 30 min. The temperature was lowered to 580° C., modified fillers and boron nitride were added, stirred for 10 min at a speed of 60 r / min, the temperature was raised to 760° C., and the temperature was kept for 30 min. The material was cooled to room temperature to obtain a boron high thermal conductivity aluminum alloy for automobile boxes.

[0042] The amount of the modified filler is 1.35% of the total mass of aluminum, copper, silicon and magnesium, and the amount of boron nitride is 20% of the total mass of aluminum, copper, silicon and magnesium.

[0043] The modified filler is prepared by the following steps:

[0044] Step A1: dispersing carbon nanotubes in mixed acid, reacting at a speed of 300 r / min and a temperature of 105° C. for 5 hours, adjusting the pH value to be neutral, filtering and removing the filtrate, dispersing the substrate in DMF, adding DCC and KH550, reacting at a speed of 200 r / min and a temperature of 40° C. for 3 hours to obtain modified carbon nanotubes, dispersing graphene oxide in DMF, adding DCC and KH550, reacting at a speed of 200 r / min and a temperature of 40° C. for 5 hours to obtain modified graphene;

[0045] Step A2: KH570, 4-mercaptobenzimidazole and DMF are mixed evenly, and the reaction is carried out for 1.5 hours at a speed of 150 r / min and 365 nm under external irradiation to obtain intermediate 1; modified carbon nanotubes, modified graphene, intermediate 1, tetramethylammonium hydroxide aqueous solution, isopropanol and xylene are mixed, and stirred for 15 minutes at a speed of 200 r / min and a temperature of 25° C., and the pH value is adjusted to neutral, and stirring is continued for 7 days, and the filtrate is filtered to remove the filtrate, and the substrate is dispersed in a hexahydrate magnesium nitrate aqueous solution, sodium hydroxide is added, and the reaction is carried out at a speed of 800 r / min and a temperature of 105° C. for 75° C. to obtain a pretreated filler;

[0046] Step A3: The pretreated filler is placed in a muffle furnace, nitrogen is introduced, and carbonization treatment is performed for 5 hours at a temperature of 750° C., and then the filler is dispersed in a sodium hydroxide solution, stirred at a speed of 150 r / min and a temperature of 95° C. for 40 minutes, and the filtrate is filtered to remove the filtrate, and then placed in a nitric acid solution, soaked for 15 minutes, the filtrate is filtered to remove the filtrate, and placed in a copper plating solution, the pH value is adjusted to 13, and the reaction is carried out at a temperature of 65° C. for 40 minutes, the filtrate is filtered to remove the filtrate, and the filler is placed in a disodium ethylenediaminetetraacetic acid solution for passivation treatment for 20 minutes, and the filtrate is filtered to remove and dried to obtain a modified filler.

[0047] The amount ratio of the carbon nanotubes and the mixed acid described in step A1 is 1g:10mL, the mixed acid is prepared by mixing 98% sulfuric acid with 68% nitric acid in a volume ratio of 3:1, the amount of KH550 is 3.5% of the mass of the carbon nanotubes, and the molar ratio of DCC and KH550 is 1.1:1.

[0048] The molar ratio of KH570 and 4-mercaptobenzimidazole described in step A2 is 1:1, the amount ratio of modified carbon nanotubes, modified graphene, intermediate 1, tetramethylammonium hydroxide aqueous solution, isopropanol and xylene is 3g:5g:50mmo l:25mL:30mL:20mL, the amount ratio of substrate, magnesium nitrate hexahydrate aqueous solution and sodium hydroxide is 1g:10mL:0.08mmo l, and the mass fraction of magnesium nitrate hexahydrate aqueous solution is 0.75%.

[0049] The mass fraction of the sodium hydroxide solution described in step A3 is 10%, the mass fraction of the nitric acid solution is 5%, and the copper plating solution is 20g of copper sulfate pentahydrate, 40g of disodium ethylenediaminetetraacetate, 9g of formaldehyde and 0.1g of vanadium pentoxide added with water to make a 1L solution, and the mass fraction of the disodium ethylenediaminetetraacetate solution is 5%.

[0050] Comparative Example 1

[0051] Compared with Example 1, this comparative example did not add intermediate 1, and the remaining steps were the same.

[0052] Comparative Example 2

[0053] Compared with Example 1, this comparative example directly puts carbon nanotubes into a copper plating solution for copper plating, and the other steps are the same.

[0054] Comparative Example 3

[0055] Compared with Example 1, the copper plating process in this comparative example was not carried out in the copper plating solution, and the other steps were the same.

[0056] The aluminum alloys obtained in Examples 1-3 and Comparative Examples 1-3 were made into test specimens according to the standard of GB / T228.1-2010, and the tensile strength was tested using a WAW-300 microcomputer servo-controlled hydraulic universal testing machine at a tensile speed of 2 mm / min and a loading test force of 10 KN. The hardness of the aluminum alloy was measured by selecting a gear with a hardness of 62.5 kg and using a steel ball indenter for 32 seconds. The test results are shown in the following table.

[0057]

[0058] It can be seen from the above table that the present application has good tensile strength and a small drop in hardness, which ensures that the product has good mechanical properties.

[0059] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. The production process of boron high thermal conductivity aluminum alloy for automobile box, characterized by: The specific steps include: Weigh the following raw materials in percentage: 92-93% aluminum, 1-1.5% copper, 5-5.5% silicon and 0.5-1% magnesium, add aluminum, copper and silicon into a graphite crucible, melt at a temperature of 830-850° C., cool to 650-680° C., add magnesium, heat to 720-750° C., introduce nitrogen, keep warm for 20-30 minutes, cool to 550-580° C., add modified filler and boron nitride, stir for 5-10 minutes at a speed of 60 r / min, heat to 730-760° C., keep warm for 20-30 minutes, and cool the material to room temperature to obtain a boron high thermal conductivity aluminum alloy for automobile boxes; The amount of the modified filler is 1.25-1.35% of the total mass of aluminum, copper, silicon and magnesium, and the amount of boron nitride is 15-20% of the total mass of aluminum, copper, silicon and magnesium; The modified filler is prepared by the following steps: Step A1: dispersing carbon nanotubes in mixed acid, reacting, adjusting the pH value to neutral, filtering and removing the filtrate, dispersing the substrate in DMF, adding DCC and KH550, reacting to obtain modified carbon nanotubes, dispersing graphene oxide in DMF, adding DCC and KH550, reacting to obtain modified graphene; Step A2: KH570, 4-mercaptobenzimidazole and DMF are mixed and reacted to obtain an intermediate 1; modified carbon nanotubes, modified graphene, intermediate 1, tetramethylammonium hydroxide aqueous solution, isopropanol and xylene are mixed and stirred, the pH value is adjusted to neutral, stirring is continued, the filtrate is filtered to remove the filtrate, the substrate is dispersed in a hexahydrate magnesium nitrate aqueous solution, sodium hydroxide is added, and a reaction is carried out to obtain a pretreated filler; Step A3: placing the pretreated filler in a muffle furnace, introducing nitrogen, carbonizing the filler, dispersing the filler in a sodium hydroxide solution, stirring the filler, filtering and removing the filtrate, placing the filler in a nitric acid solution, soaking the filler, filtering and removing the filtrate, placing the filler in a copper plating solution, adjusting the pH value to alkaline, reacting the filler, filtering and removing the filtrate, placing the filler in a disodium ethylenediaminetetraacetic acid solution for passivation, filtering and removing the filtrate, and drying the filler to obtain a modified filler; The amount ratio of the carbon nanotubes and the mixed acid in step A1 is 1 g: 10 mL, the mixed acid is prepared by mixing 98% sulfuric acid and 68% nitric acid in a volume ratio of 3: 1, the amount of KH550 is 3-3.5% of the mass of the carbon nanotubes, and the molar ratio of DCC to KH550 is 1.1: 1; The molar ratio of KH570 and 4-mercaptobenzimidazole in step A2 is 1:1, the amount ratio of modified carbon nanotubes, modified graphene, intermediate 1, tetramethylammonium hydroxide aqueous solution, isopropanol and xylene is 3g:5g:50mmol:25mL:30mL:20mL, the amount ratio of substrate, magnesium nitrate hexahydrate aqueous solution and sodium hydroxide is 1g:10mL:0.08mmol, and the mass fraction of magnesium nitrate hexahydrate aqueous solution is 0.75%; The mass fraction of the sodium hydroxide solution described in step A3 is 10%, the mass fraction of the nitric acid solution is 5%, the copper plating solution is 20g of copper sulfate pentahydrate, 40g of disodium ethylenediaminetetraacetate, 9g of formaldehyde and 0.1g of vanadium pentoxide added to water to make a 1L solution, and the mass fraction of the disodium ethylenediaminetetraacetate solution is 5%.

2. Boron high thermal conductivity aluminum alloy for automobile box, characterized by: Produced according to the production process described in claim 1.

Citation Information

Patent Citations

  • Preparation method of star-shaped heat conducting filler with multiple heat conducting points

    CN102911402A

  • High heat conducting aluminum alloy

    CN108486432A

  • Aluminum-silicon alloy high-pressure heat treatment method and obtained product

    CN109207809A

  • Organosilicon sealant and preparation method thereof

    CN117801782A